Über die Differentialgeometrie der Strahlenkongruenzen des verallgemeinerten euklidischen Raumes - Šinkūnas, J. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ю. Шинкунас, К дифференциальной геометрии конгруэнции прямых обобщенного евклидова пространстваJ. Šinkūnas, Apibendrintos euklidinės erdvės tiesių kongruencijos diferencialinės geometrijos klausimu